The Influence of Product Quality and Location on the Purchase Decision in Bakso Damas Malang - Rahmadhani, Aisyah; Murtiyanto, Rizky Kurniawan (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
In today's globalized world, the culinary industry has seen remarkable growth, with product quality and strategic location being crucial factors. This study, titled